Natural-born cyborgs : minds, technologies, and the future of human intelligence - Clark, Andy, 1957- (Oxford University Press, 2003)
A revolutionary approach to the human mind imagines a future when humans have fully incorporated their tools and technologies into the biological reality of being human.